Improvement of cycles slip threshold for the TD method in the relative positioning - Chrisóstomo Mendonça, Caio Henrique [UNESP]; Marra Alves, Daniele Barrocá [UNESP]; Da Silva, Crislaine Menezes [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
Carrier phase and code observable are used in high accuracy positioning by global navigation satellite systems. However, the carrier phase measurement may suffer cycle slip during signal tracking. Cycles slip is a discontinuity of an integer number of cycles in the phase observable, caused by a temporary loss of lock in the receiver carrier tracking loop. Thus, cycles slip must be detected and corrected in order to obtain accurate positioning. In the present article, is proposed the definition of a new threshold of accept the cycle slip occurrence based on the values of mean and standard deviation of triple difference (TD) series data when using the detection and correction TD method. The experiments were performed with simulated data for short baseline and long baseline. For short baseline data, the classical TD method and the proposed TD method presented similar results, around 100% accuracy in the detection. For the long baseline data, 31.37% and 63.79% of detection accuracy were obtained, resulting in 49.45% and 95.32% accuracy in the correction of cycles slip when using the classical TD method and the proposed TD method. These results indicate that the proposed method is relevant in the context of detection and correction of cycle slip, especially for long baselines, as is the case in Brazil.
Melhoria no limiar de detecção de perda de ciclos para o método das TD no posicionamento relativo
Keywords: Cycle slip; GPS triple-frequency; Relative positioning